Phase transition and bandgap modulation in TiO2 nanostructures for enhanced visible-light activity and environmental applications - Rajwali Khan; Nasir Rahman; Adhimoorthy Prasannan; Khayriniso Ganiyeva; Sabyasachi Chakrabortty; Sambasivam Sangaraju (Scientific Reports, 2025)
Abstract Due to its wide-ranging applications in the climate and energy fields, enhancing the visible-light photoactivity of TiO2 nanoparticles remains a crucial challenge in photocatalysis. Interestingly, this work examined the phase transition, structural, optical, and photocatalytic characteristics of TiO2 nanoparticles doped with Al3⁺/Al2⁺ and S⁶⁺ ions. It was observed that the anatase phase (AP) dominates in pure TiO2 (100%) nanoparticles, whereas the rutile phase (RP) content increases in doped samples, reaching 20 ± 2.1% for X1 (Al = 2%, S = 2%) and falling to 12 ± 1.2% in X4 (Al = 2%, S = 8%). The introduction of Al3⁺/Al2⁺ and S⁶⁺ induces oxygen vacancies (Ovs) and alters the phase stability, as evidenced by the reduction of transformation energy to − 0.033 eV, facilitating the AP to RP transition. The effective integration of dopants indicates that a redshift and intensity in the Photoluminescence spectrum reduced by X-series nanoparticles is due to band gap reductions (from 3.23 eV for pure TiO2 to 1.98 eV for X4) and distortions in the lattice generated by Al/S doping. Raman spectroscopy results show peak broadening and shifts due to lattice strain from dopants, which validates dopant incorporation via peak shifts in Fourier-transform infrared spectroscopy. ESR study reveals paramagnetic centers in Ti3⁺-Ovs complexes, indicating defect-induced magnetic characteristics. When methylene blue (MB) dye is photocatalyzed under visible light exhibits increased activity and degradation efficiencies that are higher than pure TiO2. The pseudo-first-order kinetic results show that co-doping effectively improves photocatalytic activity. Rate constants of 0.017 min⁻1 for X4 are found to be much higher than 7.28 × 10⁻4 min⁻1 for pure TiO2 nanoparticles. Finally, anatase X-series samples degraded MB at a maximum rate of 96.4% in 150 min, outperforming undoped TiO2 (15%) and rutile-TiO2 nanoparticles (65% degradation). The fundamental mechanism explains that the photocatalytic characteristics of TiO2 are modulated by co-doping, which is why these compounds are potential candidates for environmental remediation applications.